Katılım bankalarında fıkhi danışma kurulları - Alqassimi, Nuha (My University, 2019)
ملخص البحثكثيراً ما يتم الجدال حول شرعية المعاملات البنكية الإسلامية والتشكيك بفاعلية نظام الهيئات الشرعية, لذلك تهدف هذه الدراسة إلى التعرف على نظام الهيئات الشرعية وأنواعها، وصلاحيتها، وتقييم تطبيقاتها في الواقع والمعوقات التي تواجهها. كما تتطرق الدراسة إلى استعراض نماذج الهيئات الشرعية المطبقة لبعض البلدان العربية والإسلامية. وقد أوضحت الدراسة أهمية تقنين الفتاوى الشرعية في البنوك الإسلامية، لكي تحد من الآثار السلبية لاختلاف الفتوى بين الهيئات الشرعية من مؤسسة مالية إلى أخرى, وأوضحت أهمية الاستقلالية التي يجب أن تتوفر للهيئات الشرعية، وإلزامية فتواها الصادرة.

AbstractThere is a lot of controversy about the legitimacy of Islamic banking transactions, and the questioning of the effectiveness of the system of the Sharia Supervisory Board. Therefore, this study aims at identifying the legal system, types, validity, and evaluating their applications in reality and the obstacles they face. The study also referred to the review of the models of the Sharia bodies applied to some Arab and Islamic countries. The study showed the importance of legalizing the fatwa in the Islamic banks to limit the negative effects of the difference between the fatwa and the Sharia'h Supervisory Board from one financial institution to another. and explained the importance of the independence that must be available to the legitimate bodies, and the mandatory fatwa issued.
Keywords: Bankalar ve bankacılık; Banks and banking; Islam; Islamic Banking; Islamic Economics; Islamic law; İslam hukuku; İslamiyet; Participate Banking; الهيئات الشرعية، البنوك الإسلامية، البنوك التشاركية، الاقتصاد الإسلامي Shari'ah Supervisory Board